Subhepatic inferior vena cava traumatisms.: Tratamiento - Estrugo, Roberto (Cirugía del Uruguay, 1989)
11) Treatment. The author points out three lmportant steps in the treatment of IVCT: 1) Patient transport. Resuscitation norms and the use of the antishock garment are mentioned here. 2) Arrival at the Emergency Department. Discussion on cardiopulmonary resusciation plans, the use of thorac?tomy, and pre-laparotomy aortic clamping. 3) Oeratmg room treatment. Different steps form anesthesia to surgical treatment with the different IVCT repair methods.